(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The Integrated Farming System (IFS) approach is a holistic agricultural practice that combines various agricultural activities such as crop cultivation, livestock management, aquaculture, agro forestry, and agro-processing to enhance farm productivity, sustainability, and income. This research paper focuses on the impact of IFS on doubling the income of farmers in Kanpur District, Uttar Pradesh. The study analyzes how integrating different components of farming can lead to higher yields, diversification of income sources, and reduced risks, ultimately contributing to enhanced economic stability for farmers.